Modification of CockcroftWalton-Based High-Voltage Multipliers with 220 V and 50 Hz Input for Non-Thermal Food Processing Apparatus - Anurak Jaiwanglok; Kei Eguchi; Krit Smerpitak; Amphawan Julsereewong (My University, 2020)
A design of high-voltage multipliers to generate underwater shockwaves is one of the most important factors for successfully providing non-thermal food processing in a cost-effective manner. To be capable of fully utilizing the Cockcroft–Walton-based high-voltage multipliers for underwater shockwave generation, this paper presents a topological modification of three interesting design approaches in bipolar structure for 220 V and 50 Hz AC input to generate more than 3.5 kV DC output within short time periods. In addition to Cockcroft–Walton multipliers (CWMs), the first modified scheme employs a positive full-wave rectifier (FWR) and positive voltage multiplier block (VMB), the second modified scheme employs positive/negative half-wave rectifiers (HWRs), and the last modified scheme employs a switched-capacitor AC-AC converter. To comparatively analyze their performances, the digitally controlled operations of the modified realization schemes as well as their electrical characteristic estimation based on a four-terminal equivalent model are described in detail. The effectiveness of three modified circuit configurations and the correctness of the given theoretical analysis are verified through SPICE (Simulation Program with Integrated Circuit Emphasis) simulation results. The formulas achieved from theoretical estimation are particularly useful when designing the proposed high-voltage multipliers (HVMs) because good agreement between the theoretical and simulation results can be achieved.
Keywords: Voltage multiplier; Rectifier (neural networks); Realization (probability); High Voltage; Advanced DC-DC Converters